Degradation of acid orange 7 by a controlled anaerobic-aerobic sequencing batch reactor - Buitrón, G (Water science and technology : a journal of the International Association on Water Pollution Research, 2006)
The degradation of a mono azo dye in an automated and controlled anaerobic-aerobic sequencing batch reactor (SBR) is described in this work. The experiments were conducted with a synthetic wastewater containing acid orange 7 as the model compound to degrade and glucose as the co-substrate in a molar relationship 1:40 (substrate/co-substrate). It was possible to control the anaerobic and aerobic stages, using the redox potential (ORP) as the only control variable. The strategy detects an inflection point in the ORP signal, indicating the end of the reaction. The efficiency of removal of total organic carbon was between 85% and 90%. Azo dye was removed with 85% efficiency during the anaerobic stage